CONSCIOUS MARRIAGE IN THE AL-QURAN LETTER AN-NISA AYAT 22 STUDY OF IBNU KATSIR'S INTERPRETATION - Adrianto Anto (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2025)
This study aims to describe Increasing how typically on Al-Qur’an an-nisa at 22 in tafsir of Ibnu Katsir the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first, Ibnu Katsir interpret typically on Al-Qur’an an-Nisa at 22 is prohibited and The law of typically is forbidden atau not allowed. The second, His opinion on the prohibition of marrying close relatives As an effort to prevent negative impacts that may occur in future generations Included are the risks of genetic defects caused by typically